Análise de frações antigênicas da forma metacestódea de Taenia solium, obtidas pelo Triton X-114 e por cromatografia de afinidade, no diagnóstico sorológico da neurocisticercose humana - Machado, Gleyce Alves (2008)
Neurocysticercosis (NC) caused by Taenia solium metacestodes usually affects the central nervous system and can be confused with other brain pathologies. The serological diagnosis of NC is of great importance in routine clinical management of patients because it supports the diagnosis in patients that have clinical and radiological findings compatible with this disease. The use of purified antigens has allowed the development of more sensitive and specific tests, resulting in reliable seroepidemiological and screening studies. Purification procedures using Triton X-114 (TX-114) and affinity chromatography are simple and low cost methods. The aim of this study was to characterize and to compare different antigenic fractions from crude saline extract of T. solium metacestodes obtained by phase partitioning using TX-114 and affinity chromatography for the serodiagnosis of human NC. A total of 132 serum samples were analyzed, from which 40 were of patients with NC, 62 were of patients with other parasitic diseases and 30 were from apparently healthy individuals. The crude saline extract (S) and the cyst vesicular fluid (VF) were submitted to phase partitioning using TX-114, resulting in following fractions: detergent (DS and DVF, respectively) and aqueous (AS and AVF, respectively) phases. The extract S was purified in jacalin or N-acetyl-glucosamine columns, but only the jacalin-unbound fraction was then submitted to Concanavalin A column or TX-114 partitioning. All antigens were analyzed in SDS-PAGE 12% and antigen bands were visualized by silver staining. Serum samples were evaluated for IgG detection at 1:200 dilution for ELISA and 1:100 dilution for immunoblotting. Sensitivity, specificity, diagnostic efficiency and Youden Index were calculated for ELISA. ELISA sensitivity and specificity were 92.5% and 84.8% (extract S); 92.5% and 92.4% (DS); 67.5% and 70.6% (AS); 82.5% and 85.9% (VF); 77.5% and 72.8 (DVF); 80.0 and 80.4% (AVF); 85.0% and 84.8% (jacalin-unbound fraction); 92.5% and 93.5% (Detergent jacalin-unbound fraction); 82.5% and 82.6 % (Aqueous jacalin-unbound fraction), respectively. ELISA diagnostic efficiency and Youden Index were: 87.1% and 0.77 (extract S); 92.4% and 0.85 (DS); 69.7% and 0.38 (AS); 84.8% and 0.68 (VF); 74.2% and 0.50 (DVF); 80.3% and 0.60 (AVF); 84.8% and 0.70 (jacalin-unbound fraction); 93.2% and 0.86 (Detergent jacalinunbound fraction); 82.6% and 0.65 (Aqueous jacalin-unbound fraction), respectively. By immunoblotting, all serum samples from NC patients recognized a 70-50 kDa band in the detergent jacalin-unbound fraction whereas no reactivity for this antigenic fraction was observed in serum samples from patients with other parasitoses or healthy individuals. In conclusion, the detergent jacalin-unbound fraction showed to be more sensitive and specific than other extracts, since it was able to discriminate NC patients from other parasitoses, particularly Echinococcus granulosus-infected patients.